2022
DOI: 10.1007/s11837-021-05119-6
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Platinum-Group Metals from an Unconventional Source of Catalytic Converter Using Pressure Cyanide Leaching and Ionic Liquid Extraction

Abstract: The fast depletion of critical metals in natural reserves against their increasing demands in advanced technology application presents the necessity to exploit the end-of-life/waste materials as unconventional resources. Due to a higher accumulation of platinum-group metals (PGMs) in exhausted autocatalytic converters, their recycling through an integrative bio-solvo-chemical technique has been studied. PGMs were efficiently dissolved in bio-cyanide solution produced by Chromobacterium violaceum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The critical role played by the pH level in PGM leaching processes has been reported by other authors [17,[54][55][56][57]. The optimal pH for leaching PGMs can vary significantly depending on the specific leaching process and conditions.…”
Section: Effect Of the Main Operational Variablesmentioning
confidence: 83%
See 1 more Smart Citation
“…The critical role played by the pH level in PGM leaching processes has been reported by other authors [17,[54][55][56][57]. The optimal pH for leaching PGMs can vary significantly depending on the specific leaching process and conditions.…”
Section: Effect Of the Main Operational Variablesmentioning
confidence: 83%
“…The choice of pH level is crucial in designing effective PGM leaching processes. Ilyas and Kim [56] document an upward trend in the extraction of Pt and Pd as the pH of the leach liquor decreases from 11.2, resulting in 96.4% Pt and 92.7% Pd extraction, to 10.4, where extraction rates reach 98.2% for Pt and 97.6% for Pd. Bax et al [55] reported a substantial increase in the recovery of Pt and Pd at pH 1, achieving a 99.7% recovery for Pt and 96.3% for Pd.…”
Section: Effect Of the Main Operational Variablesmentioning
confidence: 99%
“…These disadvantages of the above processes make them unsuitable for large-scale metal cyanide removal. By comparison, solvent extraction can be used to remove metal cyanides and recover valuable metals due to its large processing capacity and high selectivity [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%